Strategi Promosi Word of Mouth Communication (WOM) dalam Pemasaran Produk Simpanan pada Baitul Maal Wat Tamwil Usaha Gabungan Terpadu Nusantara Cabang Pembantu Jember Kota - Faiqoh, Dewi Elok; Siswanto, Adil (Jurnal Ragam Pengabdian, 2026)
This study was motivated by the importance of promotional strategies in increasing the marketing of savings products in Islamic financial institutions through the word of mouth communication (WOM) approach. WOM is considered effective in building public trust through interpersonal communication and direct customer recommendations. This study aimed to analyze the implementation of the WOM promotional strategy, its role in increasing the number of savings product customers, as well as the supporting and inhibiting factors in its implementation at BMT UGT Nusantara Sub-Branch Office of Jember Kota. This study used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the sub-branch manager, tellers, AOSP staff, and active customers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was tested using source and technique triangulation. The results showed that the WOM strategy was implemented through friendly service, good communication, honesty, and a pick-up service system that facilitated customer transactions. These services created customer satisfaction and positive experiences, encouraging customers to recommend the BMT to others. The WOM strategy also contributed to increasing the number of savings product customers through natural customer recommendations. Supporting factors included service quality, good interpersonal relationships, and public trust in sharia-based savings products, while the obstacles included differences in public understanding of sharia products and diverse community characteristics in receiving information.